A DEVELOPMENT OF WEB-BASED REPOSITORY SYSTEM FOR YOUTH SCIENCE CLUB (YSC) IN SENIOR HIGH SCHOOL X - Aishaa Lula; Rosalina Rosalina (IT for Society, 2021)
Youth Science Club (YSC) also known asKelompok Ilmiah Remaja(KIR)is a youth club doing aseriesofresearchactivitiesthatproducedscientificresearch work.YSC in Senior High School X is one of theprestigiousextracurricularthatalwaysproducescientificpaperworkeveryyear.Moreorless10scientific papers work in a year produced. Total 90scientific papers work collections currently they hadsince 2014. The number of scientific paper works will beincreasing since this club is currently in great demand bystudents and has a good record of achievements. Theresult of scientific paper works YSC in SHS X mostlyprinted, then store at chemistry laboratory and library.Meanwhile for the digital files, only the club adviser andYSC members (who created scientific paper works) savethe digital files on their respective devices. So, the digitalfiles scattered across various devices make storing andfinding files a tough process.Based on that problem,this thesis intends to solve the problem by developing aweb-based repository system to help sustain the digitalasset of YSC in SHS X.